A 1200+ year reconstruction of temperature extremes for the northeastern Mediterranean region. (13th December 2018) - Klippel, Lara; Krusic, Paul J.; Konter, Oliver; St. George, Scott; Trouet, Valerie; Esper, Jan
Abstract : Proxy evidence is necessary to place current temperature and hydroclimatic changes in a long‐term context and to assess the full range of natural and anthropogenic climate forcings. Here, we present the first millennium‐length reconstruction of late summer (August–September) temperature variability for the Mediterranean region. We compiled 132 maximum latewood density (MXD) tree‐ring series of living and relict Pinus heldreichii trees from a network of four high‐elevation sites in the Pindus Mountains of Greece. Forty series reach back into the first millennium and the oldest sample dates to 575 CE. At annual to decadal scales, the record correlates significantly with August–September temperatures over the Balkan Peninsula and northeastern Mediterranean ( r 1950–2014 = 0.71, p < 0.001). We produce two reconstructions emphasizing interannual and decadal scale variance over the past millennium. Analysis of temperature extremes reveals the coldest summers occurred in 1035, 1117, 1217, 1884 and 1959 and the coldest decades were 1061–1070 and 1811–1820. The warmest summers occurred in 1240 and 1474, and the warmest decades were 1141–1150 and 1481–1490. Comparison of this new reconstruction with MXD‐based summer temperature reconstructions across Europe reveals synchronized occurrences of extreme cool summers in the northeastern Mediterranean, and an antiphase‐relationship with warm summer temperatures over the British Isles and Scandinavia. This temperature dipole is related to anomalies in the latitudinal position of the North Atlantic Jet. Despite the representation of common atmospheric forcing patterns, the occurrence of warm extremes is limited to few events, suggesting potential weaknesses of MXD to record warm temperature anomalies. In addition, we acknowledge problems in the observational data to capture local temperature variability due to small scale topographic differences in this high‐elevation landscape. At a broader geographical scale, the occurrence of common cold summer extremes is restricted to years with volcanically induced changes in radiative forcing. Abstract : Site characteristics. (a) Typical shape of the oro‐mediterranean ecotone (2, 000–2, 200 m a.s.l.) at the eastern foothills of Mt. Smolikas in northwestern Greece with open stands of Pinus heldreichii forming the tree‐line and (b) sampling of relict material. (c) Map of the of the study region and (d) climate diagram of the meteorological station in Ioannina (39.70°N, 20.80°E, 488 m a.s.l.) for the period 1961–1990.